RETRACTION NOTICE TO “The Effect of Multiple Sequential Activities Stim-ulation Techniques to Early Childhood Language Acquisition During Social Restriction of COVID-19 Policy in Indonesia” - Siti Salamah; Fathiaty Murtadho; Yumna Rasyid (Future Science, 2022)
This article entitled “The Effect of Multiple Sequential Activities Stimulation Techniques to Early Childhood Language Acquisition During Social Restriction of COVID-19 Policy in Indonesia” (2022), authored by Siti Salamah, Fathiaty Murtadho, and Yumna Rasyid, published in Vol. 3, No. 1 of Basic and Applied Education Research Journal 3(1): 22 – 27 has been retracted as requested by the authors.